Nursing Care Performance, Social Support, and Postoperative Patient Satisfaction - Fatoni Fatoni; Milawati Lusiani; Agus Sustiyono (Journal of Community Health Provision, 2026)
This study aimed to examine the association between nursing care performance and postoperative patient satisfaction and to explore the potential mediating role of social support in this relationship. A quantitative cross-sectional study was conducted among 192 postoperative patients from public and private hospitals in Serang Regency and Serang City, Indonesia. Data were collected using structured questionnaires and analyzed using descriptive statistics, linear regression, path analysis, and independent sample t-tests. The findings indicated that nursing care performance was positively and significantly associated with postoperative patient satisfaction. Social support was also positively associated with patient satisfaction and demonstrated a potential mediating role in the relationship between nursing care performance and patient satisfaction. Nursing care performance was categorized as very high, social support as moderate, and patient satisfaction as high. No statistically significant differences in patient satisfaction were observed according to hospital type or geographical location. The findings suggest that both nursing care performance and social support are important factors associated with postoperative patient satisfaction. The discrepancy between very high nursing care performance and moderate social support highlights opportunities to strengthen psychosocial support during recovery. Healthcare institutions are encouraged to maintain high standards of nursing care while enhancing family involvement, therapeutic communication, patient education, and other psychosocial support strategies to improve postoperative care experiences.